Screening for amplification genomic loci and genes associated prognosis in gastric cancer - Xiao-Hong Wang; Lian-Hai Zhang; Jia-Fu Ji (临床与病理杂志, 2026)
Objective: We used a high-resolution array-based comparative genomic hybridization (aCGH) coupled with patient clinical information to identify prognosis-related genomic loci and genes. Methods: aCGH coupled with patient clinical information was applied to identify prognosisrelated loci and genes with high-frequency recurrent gains in 129 GC cases. The candidate loci and genes were validated using an independent cohort of 384 cases through branched DNA signal amplification analysis. Results: A copy number gain of three chromosome regions, namely, 8q22, 8q24and 20q11-q13, conferred poor survival for patients. In addition, MYC, TNFRSF11B, ESRP1, CSE1L and MMP9 were found to be well correlated. Further validation verified that only MYC and TNFRSF11B within 8q24 are related to survival. Patients with gains in both MYC and TNFRSF11B presented poorer survival than those with no gains, particularly those with non-cardia GC. Gains in both of these genes were also a significant independent prognostic indicator. Conclusion: Copy number gains in MYC and TNFRSF11B located at 8q24are associated with survival in GC, particularly noncardia GC.